Conformation Transition Kinetics of Silk Fibroin in Aqueous Solution Explored Using Circular Dichroism Spectroscopy. Issue 8 (18th February 2021) - Lee, Sora; Kim, Soo Hyun; Jo, You‐Young; Ju, Wan‐Taek; Kim, Hyun‐Bok; Kweon, HaeYong
Abstract: Silk fibroin (SF) solution is characterized by its structural instability. Despite many efforts to uncover the structural features of SF, the time‐dependent conformation transition behaviors of SF solutions prepared under different conditions have not yet been investigated in detail. Therefore, in this study, the conformation transition changes of SF were dynamically monitored in an aqueous state using circular dichroism (CD) spectroscopic analysis. CD spectra of SF continuously change during ethanol treatment and storage, showing growth with a positive peak at 197 nm and a negative peak at 218 nm, consistent with β‐sheet development. Additionally, the time points for SF to begin and complete changing structures, including its changing rates, were confirmed. In particular, the transition kinetics follow the one‐phase exponential decay function, quantitatively showing a longer dissolution time and lower storage temperature delay for the development of β‐sheets with lower rate constants. In conclusion, our investigation provides useful information on the intrinsic properties of SF and environmental factors that can affect the structural stability of SF. Abstract : Circular dichroism spectroscopy confirmed that silk fibroin (SF) continuously changes its conformation over the exposure time to stimuli. The transition kinetic curves follow a one‐phase exponential decay function, showing that a longer dissolution time and lower storage temperature result in delayed development of the β‐sheet and improved structural stability of SF.